Differences in lower quarter Y-balance test with player position and ankle injuries in professional baseball players. (11th March 2019) - Ryu, Chang Hyun; Park, Jungu; Kang, Mina; Oh, Joo Han; Kim, You Keun; Kim, Yong Il; Lee, Ho Seong; Seo, Sang Gyo
Purpose: Although there has been research about the correlation between ankle injury and Y-balance test (YBT) conducted in other sports, there has been a lack of research on the correlation between ankle injury among baseball players and YBT scores or on differences in scores according to baseball positions. This study focused on professional baseball players as its subjects with the aims of analyzing the correlation between YBT and ankle injury and assessing differences in YBT between baseball positions. Methods: Age, height, weight, body mass index, and spine malleolar distance of 42 professional baseball players were measured. YBT measurements were performed using each foot in three distinct directions. YBT normalized reach distances, composite score, and reach asymmetry were analyzed. Results: The mean right posteromedial normalized reach distances for the player positions were significantly different between the pitchers (107.7%) and infielders (113.7%) ( p = 0.028). For the composite score, the difference between the pitchers (92.3%) and infielders (95.0%) was statistically significant ( p = 0.048). The anterior reach asymmetry was larger in the injured group than in the noninjured group ( p = 0.041). Conclusion: This study shows that YBT can be used as a way of evaluating the injury of baseball players. It also shows the reference value of YBT according to position in professional baseball players. This study could be useful for the treatment of ankle injury of baseball players. Level of evidence: Level 3.